Stage-dependent loss of cortical gyrification as Parkinson disease "unfolds". (22nd March 2016) - Sterling, Nicholas W.; Wang, Ming; Zhang, Lijun; Lee, Eun-Young; Du, Guangwei; Lewis, Mechelle M.; Styner, Martin; Huang, Xuemei
Abstract : Objective: Nigrostriatal terminal losses are known to progress most rapidly in early-stage Parkinson disease (PD) and then plateau, whereas cortical pathology continues and may provide a better marker of PD progression in later stages. We investigated cortical gyrification indices in patients with different durations of PD, since cortical folding may capture complex processes involving transverse forces of neuronal sheets or underlying axonal connectivity. Methods: Longitudinal cohort structural MRI were obtained at baseline, 18 months, and 36 months from 70 patients with PD without dementia and 70 control participants. Cortical local gyrification index (LGI) was compared between controls and PD subgroups based upon duration of illness (DOI, <1 year [PDE, n = 17], 1–5 years [PDM, n = 19], >5 years [PDL, n = 24]) and adjusted using false discovery rate. Associations between LGI and clinical measurements were assessed using multiple linear regression. Areas having significantly reduced LGI also were analyzed using baseline data from a newly established cohort (PD n = 87, control n = 66) to validate our findings. Results: In the longitudinal cohort, PDL had significantly reduced overall gyrification, and bilaterally in the inferior parietal, postcentral, precentral, superior frontal, and supramarginal areas, compared to controls ( p < 0.05). Longitudinally, loss of gyrification was accelerated in PDM participants, compared to controls. LGI showed robust correlations with DOI and also was correlated with PD-related clinical measurements. Similar results were obtained in the validation sample. Conclusions: Loss of cortical gyrification may be accelerated within the first few years after PD diagnosis, and become particularly prominent in later stages. Thus, it may provide a metric for monitoring progression in vivo.